2014
DOI: 10.1093/mnras/stu2153
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the spectral lag of short and long gamma-ray bursts and its relation with the luminosity

Abstract: We investigated the rest frame spectral lags of two complete samples of bright long (50) and short (6) gamma-ray bursts (GRB) detected by Swift. We analysed the Swift /BAT data through a discrete cross-correlation function (CCF) fitted with an asymmetric Gaussian function to estimate the lag and the associated uncertainty. We find that half of the long GRBs have a positive lag and half a lag consistent with zero. All short GRBs have lags consistent with zero. The distributions of the spectral lags for short an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 46 publications
(61 reference statements)
3
85
0
Order By: Relevance
“…Short GRBs (S-GRBs) are consistent with negligible spectral lag (Norris et al 2001;Norris & Bonnell 2006;Bernardini et al 2015), while L-GRBs have positive, null or negative lag (Ukwatta et al 2012;Bernardini et al 2015). No clear physical motivation helps one in accounting for the spectral lag contribution in each single case (for possible interpretations of the spectral lag see Dermer 1998;Kocevski & Liang 2003;Ryde 2005;Peng et al 2011;Salmonson 2000;Ioka & Nakamura 2001;Dermer 2004;Shen et al 2005;Lu et al 2006;Guiriec et al 2010Guiriec et al , 2013Mochkovitch et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short GRBs (S-GRBs) are consistent with negligible spectral lag (Norris et al 2001;Norris & Bonnell 2006;Bernardini et al 2015), while L-GRBs have positive, null or negative lag (Ukwatta et al 2012;Bernardini et al 2015). No clear physical motivation helps one in accounting for the spectral lag contribution in each single case (for possible interpretations of the spectral lag see Dermer 1998;Kocevski & Liang 2003;Ryde 2005;Peng et al 2011;Salmonson 2000;Ioka & Nakamura 2001;Dermer 2004;Shen et al 2005;Lu et al 2006;Guiriec et al 2010Guiriec et al , 2013Mochkovitch et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At variance with previous studies, we considered the largest possible sample of S-GRBs observed by the Swift/Burst Alert Telescope (BAT; Barthelmy et al 2005). This sample provides three main advantages: i) the spectral lag of S-GRBs is negligible; ii) the dispersion of the spectral lag of S-GRBs is much smaller than for L-GRBs (Bernardini et al 2015); iii) the use of a single instrument reduces also the possible systematics that arise when combining data from different instruments (Ellis et al 2008); iv) Swift/BAT enables us to perform the analysis on the largest available sample of S-GRBs with redshift.…”
Section: Introductionmentioning
confidence: 99%
“…We now fix the two energy bands, 1 [100-150] keV and 2 keV, which were used to obtain the lags in the source frame by Ukwatta et al (2012), Bernardini et al (2015), and Heussaff (2015), and in Fig. 3a we represent the lag as a function of the peak energy of the pulse spectrum.…”
Section: Fixed Energy Bands Different E Pmentioning
confidence: 99%
“…Ukwatta et al (2012), Bernardini et al (2015), and Heussaff (2015) recently constructed samples of rest-frame lags for long bursts with known redshift observed with the Swift satellite.…”
Section: Monte Carlo Approach To the Observed Lag-luminosity Relationmentioning
confidence: 99%
See 1 more Smart Citation